Report African Standards and Guidelines for Quality Assurance awareness in Africa - HAQAA Initiative (HAQAA Initiative, 2023)
As a follow-up to the development of the African Standards and Guidelines for Quality Assurance (ASG-QA) under the HAQAA initiative (Harmonisation, Quality Assurance and Accreditation in Africa), initiated by the European Union in the context of the Africa-EU Partnership, many activities were carried out by the implementing consortium of HAQAA and stakeholders, to promote and implement the ASG-QA. For example, evaluations of quality assurance agencies and ‘consultancy visits’ to emergent agencies were organised in some African countries to test the relevance of the ASG-QA and to give the structures of the countries concerned the opportunity to position themselves in relation to them. To further facilitate the use of the ASG-QA, a Guide on how to use the ASG-QA in higher education institutions and quality assurance agencies was developed. And, as the first collective initiative across linguistic lines, a dissemination activity of three organisations from different African regions was launched in the last year of the second phase of the HAQAA Initiative, to assess the widespread use of the ASG-QA in Africa. This project, hereafter called the ‘QA Network dissemination project’, was implemented by two QA networks and one national QA Agency, namely the Francophone African Network of National Quality Assurance Agencies (RAFANAQ), the East African Quality Assurance Network (EAQAN) and the National Quality Assurance Council of Mozambique (CNAQ).
Outcome of the Quality Assurance Network Dissemination Project
Keywords: Quality Assurance; Higher Education